(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
The Cold War was a period of military tensions in the world after the Second World War among the so-called M>estern world led by the USA and its NATO allies and the communist world led by the Soviet Union and its satellite states allies. It began after the success made by the Anti-Hitler coalition against Nazi Germany and its allies. USA and USSR after the War became two super powers which had substantial political and economic differences. USSR after the war created the Eastern Block countries and made satellite states out of them. During the Cold War, there was no global conflict as both sides had nuclear weapons and its use would lead to the destruction of humanity. Therefore this War is not political in technical and legal sense, neither a peace. The large forces from a position of strength resolved the problems without having to break out a general military conflict. The world after the War was based on mutual accusations from both superpowers which expressed uncertainty. USA accused USSR for violent spread of communism and USSR blamed USA for imperialism and counterrevolution. Both sides tried to gain support from other countries. The goal was to protect its own interests through the most countries supporters.